2014
DOI: 10.1007/s10637-014-0193-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy syndrome induced by enzalutamide in a patient with castration-resistant prostate cancer

Abstract: Summary Posterior reversible encephalopathy syndrome (PRES) is a clinical/radiological syndrome characterized by symptoms that can include seizure, headache, impaired vision and hypertension, and can be confirmed by magnetic resonance imaging. Numerous reports have emerged that describe PRES in cancer patients. The list of medications linked to PRES can include traditional cytotoxic chemotherapeutics (e.g., cisplatin, cyclophosphamide, and high-dose corticosteroids), newer agents that target the vascular endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…37 Moreover, potential reasons for treatment discontinuation could include the development of central nervous system (CNS) conditions such as fatigue and posterior reversible encephalopathy syndrome events, though the latter is infrequent. 15,38 In the literature, advanced prostate cancer has often been associated with CNS conditions such as fatigue. 39,40 Results from various trials evaluating the effectiveness of ENZ reported an association between ENZ and several CNS complications, particularly fatigue.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…37 Moreover, potential reasons for treatment discontinuation could include the development of central nervous system (CNS) conditions such as fatigue and posterior reversible encephalopathy syndrome events, though the latter is infrequent. 15,38 In the literature, advanced prostate cancer has often been associated with CNS conditions such as fatigue. 39,40 Results from various trials evaluating the effectiveness of ENZ reported an association between ENZ and several CNS complications, particularly fatigue.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…The third case includes a patient on several medications during the time of Ra-223 administration including enzalutamide. Single case reports of posterior reversible encephalopathy syndrome (PRES) have been observed in individuals receiving enzalutamide [ 26 ]. PRES is characterized by seizure, headache, impaired vision, and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Enzalutamide (and other second-generation antiandrogens) frequently causes blurred vision, which is usually self-limiting. In rare cases, enzalutamide can cause PRES (posterior reversible encephalopathy) syndrome with headache, seizures, impaired vision, and hypertension [ 26 , 27 ]. Although definite evidence is lacking, enzalutamide-mediated GABA receptor inhibition in the central nervous system (CNS) has been suggested as a potential mechanism [ 27 ].…”
Section: Reviewmentioning
confidence: 99%